A characterisation of cyclooxygenase activity in synaptic transmission and plasticity in the Hippocampus - Cowley, Thelma R. (Trinity College (Dublin, Ireland). School of Psychology, 2006)
We used in vivo electrophysiological techniques to investigate the role played by cyclooxygenase (COX) enzymatic activity in synaptic transmission and plasticity. The use of selective pharmacological antagonists for the COX-1 and COX-2 isoforms enabled us to differentiate the functions of these two very similar enzymes in the dentate gyrus of the hippocampal formation, using a model of memory storage - long¬term potentiation (LTP). This is a process whereby repeated firing of neurons by tetanic stimulation results in an increase in synaptic efficacy and a change in synaptic weights. It is this change in synaptic weight that is postulated to underlie memory storage. We have shown that exogenous replacement of a metabolite of COX activity, PGE2, directly into the hippocampus was sufficient to reverse the effects of the antagonism.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin